First record of the migrant dragonfly Pantala flavescens for mainland Italy (Insecta: Odonata) - Piretta, Lorenza; Assandri, Giacomo (Fragmenta entomologica, 2019)
In this contribution we report the observation of an individual of the migrant dragonfly Pantala flavescens (Fabricius, 1798) found at Montanaro (Piemonte, Italy) on 14 Aug 2019. This represents the first record of the species for mainland Italy and one of the very few available for Western and Central Europe before 2019. We discuss two hypotheses on the origin of this individual integrating available literature with very recent records retrieved from citizen science faunistic platforms.